Interpretationen der Aufklärung in zeitgenössischen ungarischen historischen Romanen - Laczházi, Gyula (Slavia Centralis, 2020)
Representations of the Enlightenment in Recent Hungarian Historical NovelsThe study analyses contemporary Hungarian historical novels that are set in the period around 1800 and aims to give a multi-faceted description of the ways they make the legacy of the Enlightenment legible from the perspective of the present time. The paper traces the signs of both critical and affirmative assessment of ideals and basic values of the Enlightenment in László Márton’s The Hiding-Place of Minerva, Róbert Hász’s The Proceeding of Venus, and Gergely Péterfy’s The Stuffed Barbarian. The increasing literary interest in the period around 1800 these novels are set in is deeply connected to recent debates concerning the values of Enlightenment modernity. At the same time, the representations of the period these works present can be regarded as contributions to cultural memory of the past. The analysis show that these novels differ not only thematically, but also regarding the implied role of the reader.
Keywords: enlightenment; historical novel; progress; Habsburg Monarchy; secret society